Long-term Exposure to Oxidant Gases and Mortality: Effect Modification by PM2.5 Transition Metals and Oxidative Potential. Issue 6 (27th September 2022) - Toyib, Olaniyan; Lavigne, Eric; Traub, Alison; Umbrio, Dana; You, Hongyu; Ripley, Susannah; Pollitt, Krystal; Shin, Tim; Kulka, Ryan; Jessiman, Barry; Tjepkema, Michael; Martin, Randall; et al.
Abstract : Background: Populations are simultaneously exposed to outdoor concentrations of oxidant gases (i.e., O3 and NO2 ) and fine particulate air pollution (PM2.5 ). Since oxidative stress is thought to be an important mechanism explaining air pollution health effects, the adverse health impacts of oxidant gases may be greater in locations where PM2.5 is more capable of causing oxidative stress. Methods: We conducted a cohort study of 2 million adults in Canada between 2001 and 2016 living within 10 km of ground-level monitoring sites for outdoor PM2.5 components and oxidative potential. Ox exposures (i.e., the redox-weighted average of O3 and NO2 ) were estimated using a combination of chemical transport models, land use regression models, and ground-level data. Cox proportional hazards models were used to estimate associations between 3-year moving average Ox and mortality outcomes across strata of transition metals and sulfur in PM2.5 and three measures of PM2.5 oxidative potential adjusting for possible confounding factors. Results: Associations between Ox and mortality were consistently stronger in regions with elevated PM2.5 transition metal/sulfur content and oxidative potential. For example, each interquartile increase (6.27 ppb) in Ox was associated with a 14.9% (95% CI = 13.0, 16.9) increased risk of nonaccidental mortality in locations with glutathione-related oxidative potential (OP GSH ) above the median whereas a 2.50% (95% CI = 0.600, 4.40) increase was observed in regions with OP GSH levels below the median (interaction P value <0.001). Conclusion: Spatial variations in PM2.5 composition and oxidative potential may contribute to heterogeneity in the observed health impacts of long-term exposures to oxidant gases.